Chemical constituents of stem bark of shorea faguetiana - Rohaiza, S; Yaacob, W.A; Din, L.B; Nazlina, I (Universiti Kebangsaan Malaysia, 2012)
A phytochemical investigation on the acetone extract of the stem bark of Shorea faguetiana was conducted. The isolation of the chemical compounds was carried out by different chromatographic techniques and their structures were elucidated by spectroscopic methods including UV, IR, NMR and MS, and also by comparison with the literature. Five oligostilbenes were isolated and identified as (-)-ε-viniferin, (-)-α-viniferin, (-)-laevifonol, (-)-ampelopsin E and (-)-hopeaphenol.